Antioxidant Activity of Flavonoids in LPS-Treated IPEC-J2 Porcine Intestinal Epithelial Cells and Their Antibacterial Effect against Bacteria of Swine Origin - Dóra Kovács; Zita Karancsi; Orsolya Farkas; Ákos Jerzsele (MDPI AG, 2020)
Beneficial effects of flavonoids are widely known in human medicine, but less information is available about their veterinary usage. Based on their antioxidant and antibacterial activity, proanthocyanidins (PAs) and luteolin (LUT) might be used in the prevention and treatment of gastrointestinal infections in swine. In this study, in vitro beneficial effects of grape seed oligomeric proanthocyanidins (GSOPs) and LUT were investigated against bacterial endotoxin (LPS)-induced oxidative stress in IPEC-J2 porcine epithelial intestinal cells. Furthermore, antibacterial effects of GSOP and LUT were assessed against field isolates of Escherichia coli and Salmonella enterica ser. Typhimurium. Both GSOP and LUT were found to possess potent in vitro antioxidant activity in LPS-treated IPEC-J2 cells; furthermore, they showed a bacteriostatic effect against the tested bacterial strains of porcine origin. Both flavonoids seem to be effective in the protection of porcine intestinal epithelial cells against Gram-negative bacteria in vitro, but further in vivo studies are necessary to confirm these activities and to establish their optimal dosage regimen for future usage in veterinary practice.